Pengembangan Paket Pelatihan “Ground, Understand, Revise, Use (GURU)-Karier” untuk Meningkatkan Efikasi Diri Karier Calon Konselor - Setyaputri, Nora Yuniar; Lasan, Blasius Boli; Permatasari, Devi (Jurnal Kajian Bimbingan dan Konseling, 2016)
Guidance and Counseling is a system, which includes: problems, objectives, techniques, media and evaluation. A technique in implementing BK services cannot stand alone, therefore it needs to be accommodated by a medium. The function of guidance and counseling media is to expedite the process of implementing the guidance and counseling services. The technique chosen is the GURU Process (Ground, Understand, Revise, Use) while the media chosen is the "GURU-Career" training package. The aim of this research is to produce guidance and counseling media in the form of a "GURU-Career" Training Package that can be accepted theoretically and practically. This research uses research and development methods. The development model used is the Borg & Gall 1983 research and development model. This training package consists of 2 copies, namely 1) a training package for counselors and 2) a training package for counselors. Based on the results of the BK expert test, educational media development expert test, user test and small group test on 6 BK students (counselor candidates) it can be concluded that the "GURU-Career" training package has proven worthy of being accepted as a guidance and counseling medium to increase candidate career self-efficacy. counselor. Suggestions put forward in this research include that guidance and counseling lecturers and guidance and counseling teachers/counselors can use the "GURU-Career" training package to increase the career self-efficacy of prospective counselors, can use this training package as a means of personal development for counselors, for future researchers can use broader research subjects, changing the research design to experimental research with a control group as well as guidance and counseling action research.